Pencatatan Skor Pertandingan Bulutangkis Menggunakan Arduino yang Dapat Dipantau via Aplikasi - Gerry Eka; Agustinus Noertjahyana; Resmana Lim (Jurnal Infra, 2020)
The recording of scores in badminton is important in a badminton match. With the score records, the players, referees and spectators can easily know the score of the match both ongoing and completed matches. So far, score records in badminton matches usually uses a manual scoreboard that needs to be written or used manually. Therefore, another alternative is needed to facilitate the recording of scores in badminton matches.In this thesis a badminton match score recording system will be made using Arduino technology which is connected to an application that can help players, referees and spectators to be able to find out the match scores.The final result of this thesis is a tool that has been designed and an application to facilitate players, referees and spectators in a badminton match to find out the match scores.